An analytical economic study of the production of cut flowers in the Syrian coast (lilium model) - سرحيل, زياد (Latakia University Journal -Biological Sciences Series, 2023)
Due to the great economic importance of cut flowers (Lilium) as one of the important crops, which were introduced to Syrian agriculture as one of the most important or complementary crops, especially in the coastal strip, as one of the hoped-for areas for the spread of this agriculture. The study focused on the economic advantages and the material returns from the production of Chrysanthemum in the Syrian coast through the study of production costs and indicators of economic efficiency based on data and data collected from the sample of 12 farmers, Market prices prevailing in 2022, has been pursued in this research to achieve the following objectives: - Studying the reality of the production of ornamental plants and cut flowers in Syria in general, and the Syrian coast in particular. - Calculation of the production costs of the Lilium in the Syrian coast. - Calculation of some indicators of the economic calendar for the production of Lilum in the Syrian coast. As a result of the study, the following results were obtained: The average annual net profit realized from the plastic house planted with Al- Lilum was 16369614 SP /year. Profitability ratio in relation to invested capital was 36.4%, and compared to production costs 166.5%. The Chrysanthemum Capital Recovery Time Index was 2.7 years, and the economic efficiency index was 2.66